Upaya Penurunan Nyeri Pada Pasien Tn.S Dengan Spondilitis Tuberkulosis Di RS Ortopedi Prof.Dr.R.Soeharso Surakarta - MARLINA, HASTI; , Fahrun Nur Rosyid, S.Kep.,Ns.,M.Kes (2016)
Pain is one of the main symptoms that occur in patients with spondylitis tuberculosis (TB). The most frequently affected are the lower thoracic vertebra and thoracolumbar spine. Some nursing plans that can be given in managing pain is to teach non-pharmacological techniques. One non-pharmacological techniques to do that is by giving a warm compress. A warm compress is an act of self-nurses form of a liquid or a tool that provides a sense of warmth and aims to reduce the pain. The purpose of this scientific publication is that authors can find a general overview of nursing care with spondylitis TB and report on non-pharmacological techniques that can be handling of pain in patients Tn.S with a diagnosis of spondylitis TB in Parang Seling class in Orthopaedic Hospital Prof.Dr.R.Soeharso of Surakarta. The method used in the writing of this publication that is using descriptive method with case study approach where the obtained data the authors conducted interviews with patients and families, make observations, conduct a physical exam and look at the record of the development of patient records. The results obtained after nursing care for 3 x 24 hour decrease pain scale before and after the intervention, it is proved on the last day of the patient's pain scale decreased from scale 7 on the first day to 4. The conclusion obtained is the problem of acute pain in patients can be resolved in part so that planning intervention continues. And the expected scientific publications can be used as a recommendation to reducing pain in patients with spondylitis TB.